Immunopathology in drug resistant mesial temporal lobe epilepsy with different types of hippocampal sclerosis. (4th May 2018) - Tezer, F. Irsel; Firat, Aysegul; Tuzun, Erdem; Unal, Isik; Soylemezoglu, Figen; Bilginer, Burcak; Kaymaz, Figen; Oguz, Kader K.; Saygi, Serap
ABSTRACT: Purpose: There is evidence that autoimmunity has a specific role in temporal lobe seizures of limbic encephalitis patients. Our aim in this study was to investigate any histopathological clues of autoimmune process in refractory temporal lobe epilepsy (TLE) patients with different pathologically proven hippocampal sclerosis (HS) types. Methods: 22 patients who had undergone epilepsy surgery due to mesial TLE-HS were included. The sera of patients are tested for neuronal antibodies to N-methyl-D-aspartate receptors (NMDAR), leucine-rich, glioma inactivated 1 (LGI1), contactin-associated protein 2 (CASPR2), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR), gamma-aminobutyric acid B receptor (GABAB R) and glutamic acid decarboxylase (GAD). Pathological and immunohistochemical investigations including neuronal nuclei (NeuN), NMDAR, GAD, glial fibrillary acidic protein (GFAP), CD8 + -CD3 + lymphocytes and immunoglobulin G (IgG) were done. Patients were grouped according to type of HS. Clinical features and immunohistochemical changes were defined in these groups. Results: Available sera of 15 patients did not have any neuronal antibodies. Thirteen of 22 patients had HS type 1, three had HS type 2 and two had HS type 3. According to immunohistochemical investigations CD3 + and CD8 + T cell infiltration was more prominent in the hippocampus of patients with classical HS (International League Against Epilepsy (ILAE) Type 1 HS) and there was a significant negative correlation between epilepsy duration and numbers of CD3 + -CD8 + lymphocytes in temporal lobe parenchyma. Conclusion: The role of T cell-mediated immunopathology and immunopathological difference in a variety of drug resistant TLE-H2S patients was suggested. These findings can be helpful in understanding the epileptogenicity of HS.